2017
DOI: 10.1177/1077559517733816
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Childbearing Among Young Adults Who Experienced Foster Care

Abstract: This study explores rates of early pregnancy and parenthood among a sample of young adults ( N = 215), ages 18-22, with a history of foster care. The study also compares the educational attainment, financial resources, and homelessness experiences of young adults who became parents to those who did not. By age 21, 49% of the young women became pregnant, and 33% of young men reported getting someone pregnant. Over a quarter of participants experienced parenthood, which was associated with lower educational atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
58
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 18 publications
4
58
3
Order By: Relevance
“…Birth rates among youths in foster care have been the subject of several recent investigations (Combs, Begun, Rinehart, & Taussig, ; Font, Cancian & Berger, ; King, ; Shpiegel & Cascardi, ). Although specific estimates have varied across samples, most existing studies indicate that females with foster care backgrounds exhibit birth rates two to three times higher than their counterparts in the general population (Eastman, Palmer, & Ahn, ; Font et al, ; Svoboda, Shaw, Barth, & Bright, ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Birth rates among youths in foster care have been the subject of several recent investigations (Combs, Begun, Rinehart, & Taussig, ; Font, Cancian & Berger, ; King, ; Shpiegel & Cascardi, ). Although specific estimates have varied across samples, most existing studies indicate that females with foster care backgrounds exhibit birth rates two to three times higher than their counterparts in the general population (Eastman, Palmer, & Ahn, ; Font et al, ; Svoboda, Shaw, Barth, & Bright, ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that adolescent childbirth is linked to adverse outcomes for mothers, including educational underachievement, employment difficulties, and decreased economic self‐sufficiency (e.g., Barnet, Liu, & DeVoe, ; Boden, Fergusson, and Horwood, 2008; Furstenberg, ). Yet few studies have explored the outcomes of adolescent mothers with current or past foster care involvement (Eastman & Putnam‐Hornstein, ; Eastman, Schelbe, & McCroskey, ; Font et al, ; Combs et al, ; Shpiegel & Cascardi, ; Schelbe & Geiger, ). The limited research on this topic has produced inconsistent findings, with some studies describing heightened challenges among young women who have given birth (e.g., Combs et al, ; Shpiegel & Cascardi, ) whereas others depicting motherhood as more nuanced, including both challenges and a renewed sense of purpose and motivation (e.g., Pryce & Samuels, ; Schelbe & Geiger, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations